ORGANOMETALLIC COMPLEXES AND PHOTORECORDING MEDIUM USING THE SAME - NINOMIYA HIDETAKA; ASANO KAZUO; NAGASAWA HIROKO (1995)
PURPOSE:To obtain the subject compound which is a metal complex containing imidazole derivatives, etc., each bearing substituents capable of bonding to a metal and useful as a cyan pigment of high absorption coefficient and high light-fastness in a photorecording medium with excellent photorecording characteristics and high storage stability. CONSTITUTION:An amidine represented by the formula I and bromacetophenone of the formula II are refluxed in chloroform under heating for 2 hours and the reactional product is deprotected to give an imidazole derivative of formula III. The derivative is allowed to reacted with 4-(N-ethyl-N-methylsulfonamide- ethyl)-2-methylaniline in ethyl acetate in the presence of potassium carbonate and ammonium persulfate to afford the compound of formula IV. The compound is treated with a metal salt such as nickel acetate tetrahydrate to give the objective organometallic complex of formula V (X, Y are H, a substituent capable of bonding to a metal; Z is OH, NH2, anilino; M is Ni, Co, Cu, Zn, Fe or the like).